Financial Literacy Model of Abu Keumala Al-Aziziyah Boarding School Medan - Aisyah, Siti; Nasution, Muhammad Lathief Ilhamy; Atha, Muhammad Alwan; Sabran, Iftasya Ainul Hafsah (Universitas Islam Negeri Sumatera Utara, 2024)
One of the intelligences that modern humans must have is financial intelligence, namely intelligence in managing personal assets, especially in managing personal financial assets. The respondents in this paper are students at Islamic boarding schools, where students are students who live far from their parents who are equipped with knowledge in managing finances and a certain amount of pocket money. Based on the results of the discussion, it can be explained as follows: a person's concept of financial literacy can be seen from his cognitive processes or the knowledge he has in managing finances, and in his attitude towards personal finances which will influence his financial behavior or decisions in managing finances. From the existing theory, it is adapted based on basic knowledge and financial attitudes for teenagers or those aged 13-18 years. The financial literacy model in Islamic boarding schools through values and sharing between people is able to maintain the life of an individual as a social creature who exists in a diverse community environment. This sense of solidarity and kinship will be very necessary to bring students into real life after they no longer live in Islamic boarding schools.